Pengaruh Konten Nadia Omara terhadap Persepsi dan Minat Pengikut di Platform Media - Aliya, Heny Trie Dina; Putri, Mega Aulia; Dalimunthe, Maulana Andinata (Lembaga Yasin AlSys, 2024)
This research examines the influence of Nadia Omara's content on the perceptions and interests of media platform followers. This research uses qualitative description. The results of this research show how the influence of Nadia Omara's content on the perceptions and interests of her followers on social media platforms opens up an interesting discussion space in the context of digital content. Through in-depth exploration of her content, it can be concluded that the language style, authenticity and engagement that Nadia Omara displays have a significant impact on the experience of her followers. This influence is reflected in various aspects, including increasing positive perceptions of a healthy lifestyle, mental health and happiness. A unique and distinctive language style is the main characteristic of Nadia Omara's content, creating an appeal that differentiates her from other content creators. The way he conveys each piece of information and story to the audience includes the use of an interesting language style so that it can attract the attention of the audience because the delivery is good and easy to understand. These language styles can include personification, metaphor, simile, association, litotes, and so on. High engagement and positive responses from followers also reflect Nadia Omara's success in designing content that can stimulate the interest and involvement of her followers.